Методы решения задач управления проектами технического развития сельскохозяйственных товаропроизводителей - Сидорчук, А. В.; Демидюк, Н. А.; Сиваковская, А. Н.; Гуцул, Т. Д.; Комарницкий, С. П. (НТУ "ХПИ", 2015)
Обозначены проекты по техническому развитию сельскохозяйственных товаропроизводителей. Раскрыты системные особенности исследования проектов, которые лежат в основании методов решения задач по управлению ими.

There have been proposed projects of technical development for agricultural producers. The conclusions about system features research projects that underlie the problem-solving methods of project management, have been made.
Problem-solving methods of project management of technical development for agricultural producers
Keywords: сельское хозяйство; технический потенциал; агрометеорологические условия; техническое обеспечение; системно-проектный подход; engineering; agriculture; development; projects; management; methods